Growth Analysis of Single Cell Protein (PST) Bacteria Bacillus cereus using Different Media - Nasution, Mutiara Naimi; Feliatra, Feliatra; Effendi, Irwan (Jurnal Perikanan dan Kelautan, 2021)
The Media is a material consisting of a mixture of nutrients used by microorganisms to grow and breed. Molasses and liquid waste know one of the alternative media which has the least inexpensive carbon source and is easily obtained from the waste food industry that is rich in nutrients and minerals, so it has the potential for bacterial growth of Bacillus cereus. The consetration of molasses used for growth medium is 1%; 1.5%; and 2% while liquid waste knows 8%, 10%, and 12%. Cell growth is measured by the method of Spectrophotometry, total plate count (TPC) and biomass while the incubation period of cell growth is measured every 0, 6, 12, 18, and 24 hours. The results showed from the molasses + skim milk and the tofu liquid waste + skim milk, the best medium of bacterial cell growth of B. cereus is a liquid waste know isolates K 12%. While the best growth concentrations molasses Medium bacterial B.cereus was N2% and K2%.